Hubungan Antara Orientasi Nilai (Value Orientation) dengan Perilaku Pro Lingkungan (Pro Environmental Behavior) Siswa - Ayu Awalia Rahman (IJEEM - Indonesian Journal of Environmental Education and Management, 2020)
Pro environmental behavior is a person's activity that aims to improve the quality of the environment and reduce the environmental impact of one's actions that can damage the environment which can be seen from several factors. One of the factors is value orientation. This study aims to determine the relationship between value orientation and pro environmental behavior in high school students in Jakarta. The study was conducted at 71 Jakarta High School in the first semester of the 2019/2020 Academic Year. The method used is a survey method with correlational techniques. The samples used was 100 students of class XI MIPA who were randomly selected. Data was collected using value orientation instruments (biospheric, altruistic and egoistic) with a sample reliability coefficient of 0.770 and a pro environmental behavior with a sample reliability coefficient of 0.868. Data analysis was performed with a simple linear regression test to measure the magnitude of the relationship used the Pearson Product Moment formula at a significance level of 5%. The results showed that there was a positive and significant relationship between value orientation and pro environmental behavior. The correlation coefficient of this research is 0.338. The contribution of value orientation variables to students' pro environmental behavior variables was 14.1%. Therefore, value orientation has a role in pro-environmental behavior of students.